Democracy across borders - Šabič, Zlatko (Javnost (Ljubljana), 2008)
The article focuses on international parliamentary institutions (IPIs), which generally do not receive much attention in the scholarly literature. However, it can be argued that in spite of some notable difficulties, such as the lack of membership continuity and lack of funding, IPIs can contribute to the reduction of the global/regional democratic deficit. To account for, and discuss the prospects of, increased involvement of parliamentarians in international affairs, the concepts of deliberative democracy and international public spheres have been used.
Keywords: mednarodne organizacije; politične institucije; mednarodni odnosi; democracy; demokracija